Critical Observations on the Dynamic Change in Caliber of Interarterial Segment of Anomalous Coronary Arteries on CT Angiogram with Chest Pain and Treadmill Test Findings-A Potential ‘Game changer’ Observations in Management - Mahalingam, Vijay; Gadabanahalli, Karthik; Bhat, Venkatraman (Cardiology and Cardiovascular Medicine, 2022)
Aims and background The incidence of coronary artery anomaly is rare in the general population, anomalous origin of right coronary artery being the most common. These anomalies, particularly anomalous coronary arteries with an interarterial course (ACAIAC) are potentially dangerous. Due to their low incidence, meticulous clinical and imaging guidelines have not yet been defined in assessing such patients and guiding management. Methods and results CT coronary angiograms of patients who underwent the study for exclusion of coronary artery disease were reviewed. Patients with ACAIAC were recorded. The images were reviewed and reconstructed to measure the caliber and area of the narrowest interarterial segment of ACAIAC in systolic and diastolic phases using Philips Intellispace version 12.1 software. Percentage change in area (p value 0.093) and diameter (p value 0.108) of the interarterial segment in systolic and diastolic segments, was statistically significant between anomalous coronaries with high and low interarterial course. Percentage change in area and diameter between patients with positive and negative TMT findings was also statistically significant (p<0.001 in both cases). Conclusion Significant positive correlation between change in vessel caliber in the interarterial course of coronary arteries during the cardiac cycle and TMT findings, suggests elevated risk of inducible ischemia in patients with significant vessel compression. Hence the change in vessel caliber demonstrated by CT imaging can be used as a potential criterion for risk assessment and management of patients with ACAIAC.